PENGGUNAAN RUANG PUBLIK BERBASIS KEBERSAMAAN DI PERMUKIMAN KAMPUNG BALONG KELURAHAN SUDIROPRAJAN KECAMATAN JEBRES SURAKARTA - , WORO UTAMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Public space is an important means to the society life because it facilitates the interaction between the members of society. Basically, public space is a container that can accommodate its societyâs certain activity, either individually or in group. Balong Kampong is the mixed settlement of Chinese and Javanese ethnics having uniqueness in using its public space. A variety of activities existing in Balong Kampong leads to the reduction of public space requirement. The phenomenon of limited public space can be seen from the individual activity apparently very dominant in the utilization of public space. Considering the phenomenon occurring, the use of public space has been no longer consistent with its function. The objective of research was to find out the use of public space and the values underlying the public space use. The methodology employed was inductive one with phenomenological qualitative approach. The findings in the field and discussion of research showed that the public space in Balong Kampong was used for a variety of activities including economic, social, and cultural ones. Those activities could be divided into individual and collective (common) activity. The public space used for either individual or collective activity creates the values underlying the use of public space in Balong Kampong. These values were commonness including tolerance, trust, protection, mutual guarding, sense of belonging, because they recognize and need each other. The values existing in Balong Kampong resulted from the daily life habit within the society. The conclusion of research was that the use of public space in Balong Kampong was based on the commonness within the society. The commonness (commonality) occurring in Balong Kampong resulted from the acculturation of two different cultures: Chinese and Javanese, so that in highly dense-population condition and limited space, the society is required to share many things for each activity. Key Words: Public Space, Settlement, Balong Kampong, Chinese and Javanese